+0  
 
-1
197
1
avatar+3460 

Help.

NotSoSmart  Dec 12, 2017
 #1
avatar+90053 
+1

y = x^3

 

Sequentially

 

Vertical stretch by a factor of 3  ⇒  y = 3x^3

 

Horizontal shift 4 units to the right  ⇒  y = 3(x - 4)^3

 

Vertical shift 3 units down   ⇒  y  = 3(x - 4)^3 - 3

 

 

cool cool cool

CPhill  Dec 12, 2017

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.